2022
DOI: 10.3389/fevo.2022.897197
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay and departure strategies of Semipalmated Sandpipers (Calidris pusilla) during post-breeding migration in the upper Bay of Fundy, Canada

Abstract: The Bay of Fundy, Canada is a critical staging area for Semipalmated Sandpipers (Calidris pusilla) during post-breeding migration. Recent range-wide population declines and changes in diet and migratory timing in the Bay of Fundy prompted a re-examination of staging ecology, including length of stay (last estimated in 1981), which is used in calculating migratory population estimates. We used radio-telemetry and the Motus Wildlife Tracking System to estimate individual length of stay and departure conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…However, the small amount of evidence available at present does not support this hypothesis. Radio-telemetry studies in the Bay of Fundy showed that stopover duration of Semipalmated Sandpipers has not decreased, but rather increased from ∼2 weeks in the 1980s to 3 weeks in the 2010s, during which time passage population estimates have declined by 50% (Neima 2017). Additional work is needed to estimate current lengths of stay at key stopover sites, for example using available MOTUS telemetry (Taylor et al 2017) data or other tracking technologies, and to compare these values to the fragmentary historical data.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small amount of evidence available at present does not support this hypothesis. Radio-telemetry studies in the Bay of Fundy showed that stopover duration of Semipalmated Sandpipers has not decreased, but rather increased from ∼2 weeks in the 1980s to 3 weeks in the 2010s, during which time passage population estimates have declined by 50% (Neima 2017). Additional work is needed to estimate current lengths of stay at key stopover sites, for example using available MOTUS telemetry (Taylor et al 2017) data or other tracking technologies, and to compare these values to the fragmentary historical data.…”
Section: Discussionmentioning
confidence: 99%
“…Sandpipers tagged within the Bay of Fundy remained within the Bay, while those tagged at Petit Cap either remained outside the Bay or moved into the Bay and remained there for the duration of their staging period in Atlantic Canada (see Linhart et al, in press for details). We calculated a minimum length of stay (as in Neima et al, 2022) for each bird by subtracting the deployment timestamp from the last known detection in Atlantic Canada. Detailed analyses of movement strategies, length of stay, and differences in site use between ages and tagging locations can be found in Linhart et al (in press).…”
Section: Bird Capture and Radio-telemetrymentioning
confidence: 99%
“…Recent work has found adult sandpipers using the Bay of Fundy have high within and between-year fidelity, returning to the same areas of the Bay each year (Neima et al, 2020). Additionally, the behavior, movement and diet of adult sandpipers in this habitat are well understood (e.g., MacDonald et al, 2012;Quinn and Hamilton, 2012;Neima et al, 2022). Less is known about the use of these habitats by juvenile Semipalmated Sandpipers, which may need additional time or resources to gain sufficient weight for a successful southbound migration.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the importance of departure timing of long migratory flights (Alerstam, 2009; Anderson et al., 2019; Bradarić et al., 2020; Leyrer et al., 2009; Manola et al., 2020; Neima et al., 2022; Newton, 2007; Packmor et al., 2020; Piersma & Jukema, 1990; Sapir et al., 2011; Tulp et al., 1994; Woodworth et al., 2015), but non‐migratory flights, whereby birds may relocate within the overwintering range, have received little attention, even though distances traversed can extend dozens of kilometers (Frederiksen et al., 2012; Swindells, 2019) and can involve risky barriers. Given the potential rise in extreme weather events due to climate change, it becomes crucial to comprehend the specific conditions that birds prefer during departure, even for flights within their overwintering range.…”
Section: Introductionmentioning
confidence: 99%